The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.26699/jnk.v9i2.art.p148-153
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anemia Incidence Determinants among Female Students at Islamic Boarding School Al Hidayah 2 Bangkalan

Abstract: The incidence of anemia is common in adolescent girls. Anemia causes decreased learning achievement due to lack of concentration. This research aimed to analyze the determinant factors associated with the incidence of anemia in female students at Islamic Boarding School Al Hidayah 2 Bangkalan. The research was observational analytic, a cross sectional design. The population was female students at Islamic Boarding School Al Hidayah 2 and the sample size was 72 people. The independent variables include menstrual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…UNICEF menyebutkan satu dari tujuh remaja di Indonesia mengalami obesitas (Unicef Indonesia, 2021). Sementara itu abdimas telah melakukan studi tentang indeks massa tubuh (IMT) di Pondok Pesantren Al Hidayah 2 Bangkalan dan ditemukan 3 dari 10 santriwati mengalami kelebihan berat badan (overweight dan obesitas) (Setiarsih, Kardina, Santoso, Kaunain, & Afifah, 2022). Sebuah studi menunjukkan bahwa semakin tinggi IMT akan meningkatkan persen massa lemak dan lemak viscelar yang selanjutnya akan mempengaruhi besar lingkar perut (Fatimah, Akbar, Purba, Tarawan, Nugraha, & Radhiyanti, 2017) (Susantini, 2021).…”
Section: Pendahuluanunclassified
“…UNICEF menyebutkan satu dari tujuh remaja di Indonesia mengalami obesitas (Unicef Indonesia, 2021). Sementara itu abdimas telah melakukan studi tentang indeks massa tubuh (IMT) di Pondok Pesantren Al Hidayah 2 Bangkalan dan ditemukan 3 dari 10 santriwati mengalami kelebihan berat badan (overweight dan obesitas) (Setiarsih, Kardina, Santoso, Kaunain, & Afifah, 2022). Sebuah studi menunjukkan bahwa semakin tinggi IMT akan meningkatkan persen massa lemak dan lemak viscelar yang selanjutnya akan mempengaruhi besar lingkar perut (Fatimah, Akbar, Purba, Tarawan, Nugraha, & Radhiyanti, 2017) (Susantini, 2021).…”
Section: Pendahuluanunclassified
“…6 Anemia in adolescents will cause a decrease in fitness levels which will have an impact on low productivity and sports performance. 7 In addition, iron deficiency also causes reduced attention, decreased memory and school attendance, which ultimately affects school performance in adolescents. 8,9 Several previous studies have investigated the importance of iron in cognitive function and found links between iron deficiency, diet and changes in psychological development and cognitive function.…”
Section: Introductionmentioning
confidence: 99%